SolarSPELL health and education: global solutions with local impacts - Heather M. Ross; Laura Hosman; Bruce Baikie; Emily Blau; Carol J. Simpson (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background People in remote regions of developing nations have poor health outcomes with lower life expectancy and quality of life compared to higher-resourced areas. Remote communities typically lack stable access to high-quality health services. International humanitarian and development organizations including the United States Peace Corps have a longstanding history of delivering critical services. However, limited infrastructure including access to reliable electricity or internet restricts development workers' ability to provide effective health services to rural communities. Technology that enhances health education and service delivery in remote communities may improve health outcomes by impacting health knowledge and behavior. # Methods We partnered with U.S. Peace Corps to provide portable, solar-powered educational learning libraries (SolarSPELL; www.solarspell.org) to remote communities in Pacific Island nations beginning in 2015 with Peace Corps Vanuatu educational volunteers and expanded in 2017 to include health volunteers (SolarSPELL Health). We conducted ethnographic observation and interviews with Vanuatu Peace Corps volunteers, Ministry of Health officials, and local residents of rural communities. We then conducted a comprehensive evidence review to identify current best practices for assessing and treating the most common conditions. We designed simple 2-page documents with assessment and treatment guidelines, reflecting evidence-based best practices, local culture, and resource availability. Each document was accompanied by a whiteboard video featuring simple drawings and narration designed for Peace Corps volunteers and local community members. # Results We report on findings from a pilot study focused on education for treating low back pain. Preliminary findings indicate significantly increased knowledge for Peace Corps volunteers (p<.01), along with non-significantly increased self-efficacy scores (p=.169). Interview data indicate high levels of satisfaction with the SolarSPELL technology, and widespread community utilization among Peace Corps volunteers and community residents. # Conclusions Tailored health content on the SolarSPELL platform increases knowledge about critical health topics among Peace Corps volunteers in under-resourced rural communities. The platform and education may have a positive impact on self-efficacy. However, high baseline levels of self-efficacy noted among Peace Corps volunteers may explain the failure to reach statistically significant increases in self-efficacy scores. This finding merits further study. Future work includes measuring individual and community health outcomes, quality of life, and cost benefit resulting from reductions in lost work and transfers for advanced health services. We plan continued implementation and content expansion of SolarSPELL Health in Vanuatu and additional global sites.